Local Government Policies Related to Simplification of Micro, Small and Medium Enterprises Licensing - Nurmayani Nurmayani; Ati Yuniati; Yusdiyanto Yusdiyanto; Madinar Madinar; Marlia Eka Putri (University of Udayana, 2023)
There are obstacles for business actors in establishing Micro, Small and Medium Enterprises or MSMEs. It is related to the many conditions in permissions of establishments MSMEs that make it difficult for business actors to establish MSMEs. Even it has an impact on the low interest of investors to invest. Therefore, in the government's efforts to overcome the issue of licensing for MSMEs is the establishment of Job Creation Law aims to simplify licensing for MSMEs. The research method used is Normative Juridical with a statue approach. In this study, it is known that the policies implemented in the regions are in accordance with Government Regulation No. 6 of 2021 concerning the Implementation of Business Licensing in the Regions must be in the form of a regional regulation which must be harmonized with the currently valid Government Regulations, and implemented the Online Single Submission Permission System in Lampung Province. However, currently there are no recent regional regulations that are in accordance with Government Regulations on the Implementation of Business Licensing in the Regions.